Perceptions of mothers about the quality of life of children with hydrocephalus - Carliane Evangelista Buriti Torres; Adria Marcela Vieira Ferreira; Leidiane Minervina Moraes de Sabino; Mariana Cavalcante Martins; Francisca Amanda Martins Couto; Viviane Mamede Vasconcelos Cavalcante (Rev Rene)
Objective: to understand the perceptions of mothers about the quality of life of children with hydrocephalus. Methods: qualitative research carried out in a pediatric public hospital with twelve mothers of children with hydrocephalus. Data were collected from semi-structured interviews and the content analysis was performed. Results: according to the mothers, children with hydrocephalus had a considerable motor deficit, but some managed to perform this function properly. The emotional status had not presented a significant change; and in relation to school performance, the majority was not studying in school or could not keep up with the learning rhythm of the others, however, they managed to maintain good interpersonal relationships. Conclusion: children with hydrocephalus presented deficits in motor, educational and emotional development, but they had no impairment in interpersonal relationships, according to mothers’ perceptions.